2014
DOI: 10.1155/2014/897953
|View full text |Cite
|
Sign up to set email alerts
|

Fear of Severe Pain Mediates Sex Differences in Pain Sensitivity Responses to Thermal Stimuli

Abstract: The purpose of this paper was to examine the relationship of sex and pain-related fear in pain intensity reports to thermal stimuli and whether sex differences in reported pain intensity were mediated by pain-related fear. 177 participants, 124 female (23.5 ± 4.5 years old), filled out a demographic and fear of pain questionnaire (FPQ-III). Experimental pain testing was performed using thermal stimuli applied to the lower extremity. Participants rated the intensity of pain using the numerical pain rating scale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
22
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 46 publications
(45 reference statements)
4
22
0
2
Order By: Relevance
“…Osman et al reported sex differences on the Severe and Medical Pain subscales 11. Others have reported sex differences on the Severe Pain subscale only 8. These studies clearly agree that sex differences in FOP as measured by the FPQ-III exist, and that FOP is higher in females than males.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…Osman et al reported sex differences on the Severe and Medical Pain subscales 11. Others have reported sex differences on the Severe Pain subscale only 8. These studies clearly agree that sex differences in FOP as measured by the FPQ-III exist, and that FOP is higher in females than males.…”
Section: Discussionmentioning
confidence: 75%
“…However, others have concluded that the model has a poor fit 14,16. As previously mentioned, sex differences in FOP measured by the FPQ-III have been reported repeatedly 8,11,12. Yet it should be noted that inconsistencies remain in the extant literature in this area, with some studies reporting sex differences in overall FOP, while differences are limited to the subscales in other studies.…”
Section: Introductionmentioning
confidence: 96%
“…A major finding of the study was that significant differences with respect to gender, geographic distribution, and age (tables 1, 4) were similar to those reported by Marcus et al [20], who found that pain, fatigue, and psychiatric complaints were more commonly reported in women. Reduced pain thresholds and tolerance [5,19,21] and/or increased responses to pain stimuli were observed in females [22]. Schestatsky et al [19] and Brefel-Courbon et al [11] discovered that during off-periods, patients with PD and central pain had a lower threshold for pain caused by thermal stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…[1]. Evidences of gender-specific differences exist in the receiving pain [2], [3], indicating that sex steroid hormones play significant role in pain perception. Pain threshold is the threshold at which a system can detect a painful stimulus [4], followed by signaling the pathways resulting in pain perception.…”
Section: Introductionmentioning
confidence: 99%